Innovative approach in CNC probing of oversized investment casting parts - Alexandra Negoescu (Journal of Research and Innovation for Sustainable Society)
Within this paper the main goal consisted in developing a parametric approach of the machining allowance set-up of oversized semifinished products obtained through investment casting, taking into account their high tolerance range. Through existing predefined probing cycles, it was managed configuring a system based on several variables which lead to defining the necessary steps within the machining process. The resulting NC program could be further linked to a Microsoft Excel file within which all the calculus can be done and the NC codes generated. The most important contribution consists in the fact that through this approach no further actions of the operator (measuring, calculating) are necessary, therefore plenty of errors could be avoided.